Relative abundance of yellowfin tuna Thunnus albacares (Bonnaterre, 1788) in the tropical area of the north-eastern Indian Ocean - Setyadji, Bram; Hartaty, Hety (Indian Journal of Fisheries, 2022)
The tropical area of the north-eastern Indian Ocean has historically been a prominent fishing ground for yellowfin tuna Thunnus albacares (Bonnaterre, 1788). However, low effort from either Japanese or Taiwanese fleet in the last two decades has driven some uncertainties in relative abundance estimates of yellowfin tuna, which affects the robustness of the current stock analysis for an already declined population. Hence this study was carried out to bridge the research gap by utilising the Indonesian scientific observer data from 2006-2021, which covers the north-eastern Indian Ocean. A delta-lognormal model was adopted to fit the data, with the catch per unit effort as the response variable and year, quarter, moon phase, latitude and longitude as known covariates. The optimal model was chosen using a backward method based on Akaike Information Criterion (AIC) (Akaike, 1974), Bayesian Information Criterion (BIC) (Schwarz, 1978) and the values of the coefficient of determination (R2). In general, the relative abundance of yellowfin tuna remained at a very low level, with an apparent declining trend in the first decade, followed by a slight sign of recovery in the past three years. However, the increasing trend was overshadowed by uncertainties, likely caused due to natural variation and low coverage in some years. Although the series was considered short, it managed to picture the dynamics of the abundance of yellowfin tuna in the tropical area of the north-eastern Indian Ocean, which is essential for conducting a more robust harvest strategy evaluation. Keywords: Declining stock, Fisheries-independent data, Highly migratory, Relative abundance, Scientific observer